2019
DOI: 10.1177/1179069519870182
|View full text |Cite
|
Sign up to set email alerts
|

A Further Analysis and Commentary on: Profiling Changes in Cortical Astroglial Cells Following Chronic Stress

Abstract: The neuroplasticity hypothesis of depression proposes that major depressive disorders are related to decreased hippocampal and cortical neural plasticity, which is reversed by antidepressant treatment. Astroglial cells have emerged as key mediators of neural plasticity and are involved in the cause and treatment of depression and anxiety-like behaviors. One of the ways that astroglia modulate neuroplasticity is through the formation and maintenance of perineuronal nets (PNNs). Perineuronal nets are important e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It can act at different stages of the carcinogenesis of glioma and neuroblastoma, affecting signal transduction in normal cells, promoting the proliferation and survival of cancer cells, and releasing cytokines and soluble mediators that favor tumor growth [ 50 ]. The involvement of astrocytes in depression has been reported, but valuable studies on the relationship between the genetic component of depression and glioma development and progression are still lacking [ 59 , 60 , 61 ]. Coppola et al [ 59 ] used bioinformatics analysis to further delineate the key mediators involved in the astrocyte–peripheral neural nets–depression relationship and identified important transcription factors in astrocytes [ 59 , 60 ].…”
Section: Depression As a Risk Factor For Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…It can act at different stages of the carcinogenesis of glioma and neuroblastoma, affecting signal transduction in normal cells, promoting the proliferation and survival of cancer cells, and releasing cytokines and soluble mediators that favor tumor growth [ 50 ]. The involvement of astrocytes in depression has been reported, but valuable studies on the relationship between the genetic component of depression and glioma development and progression are still lacking [ 59 , 60 , 61 ]. Coppola et al [ 59 ] used bioinformatics analysis to further delineate the key mediators involved in the astrocyte–peripheral neural nets–depression relationship and identified important transcription factors in astrocytes [ 59 , 60 ].…”
Section: Depression As a Risk Factor For Gliomamentioning
confidence: 99%
“…The involvement of astrocytes in depression has been reported, but valuable studies on the relationship between the genetic component of depression and glioma development and progression are still lacking [ 59 , 60 , 61 ]. Coppola et al [ 59 ] used bioinformatics analysis to further delineate the key mediators involved in the astrocyte–peripheral neural nets–depression relationship and identified important transcription factors in astrocytes [ 59 , 60 ]. Fibroblast growth factors (FGFs) and their receptors have been shown to be involved in the pathogenesis of neurological diseases.…”
Section: Depression As a Risk Factor For Gliomamentioning
confidence: 99%
“…Analysis of top DEGs indicated that CVS impaired perineuronal net (PNN) degradation, resulting in neuroplastic dysfunction ( Simard et al, 2018 ). Subsequently, based on the same database, Coppola et al used bioinformatics analysis to further delineate key mediators involved in the astroglial-PNN-depression relationship and found important transcription factors in astroglial cells ( Coppola et al, 2019 ). In addition to PNN, the serotonin system plays a critical role in the pathogenesis of stress, but therapies that target the stress and depression associated genes such as Tph2 and Slc6a4 (SERT) to modulate serotonin reuptake and degradation have no obvious effect in clinical trials ( Lalovic and Turecki, 2002 ; Bellivier et al, 2004 ; Oquendo et al, 2014 ).…”
Section: Narrow Sense Translatomicsmentioning
confidence: 99%
“…In this way estrogens can interact with astroglial ERs to modulate EI balance via glutamate and calcium. Work from our lab has shown that estrogen modulates the expression of GFAP and FGF2 within the cortex and that estrogen directly modulates the transcription of GFAP (Simard et al, 2018;Coppola et al, 2019). Together this data suggests a relationship between ESR1, astrocytes and depression that merits further investigation.…”
Section: Astroglia Sex and Stress Hormonesmentioning
confidence: 73%
“…Further analysis of this translatomic data using weighted gene co-expression network analysis (WGCNA) revealed five distinct modules associated with CVS-induced changes (Coppola et al, 2019). The differentially expressed genes (DEGs) within these modules were associated with ECM proteoglycans and astroglial activation, lysosome and protein transport, MAP kinases and RhoGTPases, signaling growth factors, regulation of transcription, and enrichment of metabolic pathways.…”
Section: Astroglia Sex and Stress Hormonesmentioning
confidence: 99%